2022
DOI: 10.3847/1538-4357/ac6753
|View full text |Cite
|
Sign up to set email alerts
|

Energizing Star Formation: The Cosmic-Ray Ionization Rate in NGC 253 Derived from ALCHEMI Measurements of H3O+ and SO

Abstract: The cosmic-ray ionization rate (CRIR) is a key parameter in understanding the physical and chemical processes in the interstellar medium. Cosmic rays are a significant source of energy in star formation regions, impacting the physical and chemical processes that drive the formation of stars. Previous studies of the circum-molecular zone of the starburst galaxy NGC 253 have found evidence for a high CRIR value: 103–106 times the average CRIR within the Milky Way. This is a broad constraint, and one goal of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
1
19
2
Order By: Relevance
“…It is also important to note that we only consider excitation through collisions with H 2 and therefore ignore electron collisions. A previous ALCHEMI-based study (Holdship et al 2022) found that even at the CRIRs, which will be discussed later in this article (Section 4.4), almost all hydrogen is in its molecular form under these conditions. Holdship et al (2022) found that toward GMCs 3-7 that the fractional abundance of electrons is in the range X (e −1 ) ∼ 10 −4 -10 −5 for volume densities n(H 2 )  10 5.5 cm −3 .…”
Section: Model Descriptionmentioning
confidence: 75%
See 2 more Smart Citations
“…It is also important to note that we only consider excitation through collisions with H 2 and therefore ignore electron collisions. A previous ALCHEMI-based study (Holdship et al 2022) found that even at the CRIRs, which will be discussed later in this article (Section 4.4), almost all hydrogen is in its molecular form under these conditions. Holdship et al (2022) found that toward GMCs 3-7 that the fractional abundance of electrons is in the range X (e −1 ) ∼ 10 −4 -10 −5 for volume densities n(H 2 )  10 5.5 cm −3 .…”
Section: Model Descriptionmentioning
confidence: 75%
“…Only the HNC 4-3 transition is found to have spectral neighbors, which required assessment of the amount of emission contributed by H 2 CO 5 05 -4 04 (362.736048 GHz) and HNC 4-3 v 2 = 1 (362.554351 GHz). Using the procedure described in Holdship et al (2022) we determine that these two interlopers contribute, respectively, at most 4% and 1% to the HNC 4-3 integrated emission. This contamination estimate is consistent with the multispecies LTE analysis of molecular column densities described in Martín et al (2021).…”
Section: Interloper Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6(b) shows the HOCO + /CO 2 abundance ratios in the gas phase, that vary between 10 −5 and 10 −2 for the most part. Previous ALCHEMI studies have suggested that the cosmicray ionization rates in NGC 253 are at least a few orders of magnitude higher than that in Galactic spiral-arm clouds (Holdship et al 2021;Harada et al 2021;Holdship et al 2022), which increases the HOCO + /CO 2 abundance ratios due to an increased + H 3 abundance. Although the cosmic-ray ionization rates are expected to be high, extremely high rates (ζ  10 −13 s −1 for n = 10 5 cm −3 ) would destroy HOCO + (Figure 6(c)), especially in lower-density regions.…”
Section: Hoco + /Co 2 Ratiosmentioning
confidence: 87%
“…ALCHEMI is a widefrequency, unbiased spectral scan mosaic toward the CMZ of NGC 253 at a common 1 6 resolution. This survey has discovered high cosmic-ray ionization rates (Holdship et al 2021;Harada et al 2021;Holdship et al 2022), detected a phosphorus-bearing species for the first time in an extragalactic source (Haasler et al 2022), and detected methanol masers (Humire et al 2022) in the CMZ of NGC 253. We utilize the ALCHEMI data to study the multiple transitions of HOCO + .…”
Section: Introductionmentioning
confidence: 93%